Pendampingan Pemanfaatan Zoom dan Moodle sebagai Sarana Pembelajaran Daring untuk Dosen Jurusan Ilmu Pendidikan FKIP Universitas Mataram - Muntari Muntari; Amrullah Amrullah; ‪Mohammad Archi Maulyda; Dadi Setiadi; I Made Sujana (Dedikasi Cendekia: Warta Pengabdian Pendidikan, 2025)
The COVID-19 pandemic that hit the world in 2020 has forced all educational institutions, including the University of Mataram, to quickly adapt to online learning systems. In response to this, the Laboratory of Educational Development and Learning Technology (LPPTP) FKIP, University of Mataram held online mentoring activities aimed at improving lecturers' competence in utilizing the Zoom and Moodle platforms as a means of distance learning. This activity was carried out through several interactive training sessions involving experienced facilitators and attended by all lecturers in the department. The training materials included mastery of Zoom features for synchronous lectures and the use of Moodle as a Learning Management System for managing online classes. The results of the mentoring showed an increase in the technical and pedagogical abilities of lecturers in designing and implementing online learning more effectively and interactively. Evaluation of activities through questionnaires and open discussions indicated that this activity was very useful and relevant to learning needs during the crisis. This activity is also the first step towards a more structured and sustainable digital transformation of education in the FKIP environment of the University of Mataram.